MERAYAKAN KEHIDUPAN MASYARAKAT BERISIKO DENGAN HUMOR - Isak Bendris Oematan (Marturia, 2022)
AbstractThis paper discusses the concept of a risk society which was developed by the famous German sociologist Ulrich Beck. The massive development of technology and information has brought a paradoxical impact on human life. One of those affected is religious individuals. Information implosion makes anyone free to choose and determine the things they like as well as their spiritual values without basing on the values of the religion they adhere to. In response to this, this paper offers an alternative interpretation of celebrating spirituality for post-modern Christianity, using Richard Kearney's thoughts on Atheism. This concept stakes five folds as a way to meet and encounter the Divine in the journey of life. One of the highlights in this article is the second fold which is about humor. Humor describes the natality of human life in a surplus of divine reality. This paper bases its analysis on qualitative research methods with reflective-theological studies in order to obtain theological values in the folds of humor which are then applied to the context of at-risk communities. The theory used to explain the phenomenon of humor in a society at risk is The Play Theory. The result is that the value of humor can be an alternative interpretation for contemporary Christianity in order to understand, reflect and describe the beauty of the manifestation of the Divine in all its natality and limitations, especially in the context of a risky society that is also a surplus of information, openness, schizophrenic and networking. Abstrak Tulisan ini membahas konsep masyarakat berisiko (Risk Society) yang dikembangkan oleh sosiolog kenamaan Jerman Ulrich Beck. Perkembangan teknologi dan informasi yang masif telah membawa dampak yang paradoks dalam kehidupan manusia. Salah satu yang terkena dampaknya adalah individu-individu beragama. Implosi informasi membuat siapa saja bebas untuk memilih dan menentukan hal-hal yang disukai begitu pun dengan nilai-nilai spiritualitasnya tanpa mendasarkan pada nilai-nilai dari agama yang di anutnya. Dalam menanggapi hal tersebut tulisan ini menawarkan suatu tafsir alternatif dalam merayakan spiritualitas bagi Kekristenan post-modern, dengan menggunakan pemikiran Richard Kearney tentang Anateisme. Konsep ini mempertaruhkan lima lipatan sebagai jalan untuk bertemu dan berjumpa dengan yang Ilahi dalam perjalanan kehidupan. Salah satu yang menjadi sorotan dalam tulisan ini adalah lipatan kedua yang menyoal soal humor. Humor menggambarkan natalitas kehidupan manusia di dalam surplus realitas Ilahi. Tulisan ini mendasarkan analisisnya pada metode penelitian kualitatif dengan kajian reflektif-teologis guna mendapatkan nilai-nilai teologis dalam lipatan humor yang kemudian dipakaikan ke dalam konteks masyarakat berisiko. Teori yang dipakai untuk menjelaskan fenomena humor dalam masyarakat berisiko adalah The Play Theory. Hasilnya adalah nilai humor dapat menjadi suatu tafsir alternatif bagi kekristenan masa kini guna memahami, merefleksikan dan menggambarkan keindahan manifestasi dari yang Ilahi dalam segala natalitas dan keterbatasan dirinya terutama dalam konteks masyarakat berisiko yang juga surplus informasi, keterbukaan, skozofrenik dan berjejaring.